Understanding the Importance of Sexual Consent among University Students - Hanindito Arief Buwono; Tri Hayuning Tyas (Jurnal Psikologi, 2021)
The knowledge about how young people understand sexual consent remains scant. This study aimed to understand how the university students perceived sexual consent and the importance of consent before engaging in sexual related activities with a partner. Using explanatory sequential mixed method approach, an in-depth interview was conducted to five participants following administration of survey questionnaire to obtain a general view on the issues around sexual consent. 102 active university students at the age between 18-25 years old participated in this study. The result of the questionnaire-survey was analysed with descriptive analysis and the in-depth interview data were transcribed and were analysed using the Interpretative Phenomenology Analysis (IPA). Integration of data was done to find pattern and relation between quantitative and qualitative data. Findings from this study suggest that young people, both young men and women, perceived sexual consent as important and, therefore, should be obtained before engaging in any sexual contact. While gesture and direct communication were the common techniques on communicating consent between genders, there were still difficulties in conveying the message of consent because of the subjective feeling and norms of the society.